Kajian Organologi: Kesenian Ansambel Musik Pitung Dal pada Masyarakat Alor Kalabahi - Jeny Deo Tamonob; Eko Raharjo; Slamet Haryono (Ideas Publishing, 2023)
Pitung dal is one of the arts of the Alor people which is less well known and appreciated by the people. This study aims to describe the organology of Pitung dal. The method used is descriptive qualitative through unstructured interview techniques, direct observation and documentation. The results of the study concluded that Pitung dal is an art that is played together consisting of wind instruments, namely: a) kanui pup, b) ma tawa, c) kelifang and d) feting taba inflatable. And consists of percussion instruments, namely: bo’bo and feting taba at. The art of Pitung dal music is part of the culture of the Alor people which must be preserved and appreciated through culture-based education.